please provide me answer
Attachments:
![](https://hi-static.z-dn.net/files/dae/a61ac0e40bbe1ede42f8039b2e63fca3.jpg)
Answers
Answered by
2
Answer:
this is your proof with explaination
Attachments:
![](https://hi-static.z-dn.net/files/d5f/78357b77cf1f1f1942fa61c36ca676f6.jpg)
Answered by
4
Used formulas :-
• (a - b)(a - b) = (a - b)²
• (a + b)(a - b) = a² - b²
• √a/b = √a/√b
• 1 - cos²A = sin²A
• a - b/c = a/c - b/c
• 1/sinA = cosecA
• cosA/sinA = cotA
More formulas :-
• sin²A + cos²A = 1
• sec²A - tan²A = 1
• cosec²A - cot²A = 1
• sin(A + B) = sinAcosB + cosAsinB
• sin(A - B) = sinAcosB - cosAsinB
• cos(A + B) = cosAcosB - sinAsinB
• cos(A - B) = cosAcosB + sinAsinB
• (a - b)² = a² + b² - 2ab
• (a + b)² = a² + b² + 2ab
• (a + b + c)² = a² + b² + c² + 2abc(ab + bc + ac)
Attachments:
![](https://hi-static.z-dn.net/files/d92/06b97ac60c646271f246778cf00ffa06.jpg)
Similar questions
Chemistry,
5 months ago
Computer Science,
5 months ago
Hindi,
10 months ago
Math,
10 months ago
Sociology,
1 year ago